Expression of recombinant Cap antigen of porcine circovirus type 2 in the chloroplast of Chlamydomonas reinhardtii - Song, Yiran; Lin, Youhong; Cheng, Xiaying; Li, Wei; Li, Yihong; Yang, Zongqi (Frontiers in Plant Science, 2025)
The capsid (Cap) protein encoded by the ORF2 gene of porcine circovirus type 2 is the major immunogen for the development of vaccines and can effectively reduce the incidence of porcine circovirus-associated diseases. In order to explore an efficient expression pathway of the recombinant Cap protein, using the Chlamydomonas reinhardtii chloroplast as the expression platform of the Cap protein, C. reinhardtii chloroplast expression vector pCR02 of the optimized ORF2 gene was constructed and transferred into the C. reinhardtii chloroplast using the biolistic bombardment method. After multiple rounds of resistance screening and culturing, PCR, RT-PCR, Western blotting, and ELISA were used to detect the ORF2 gene and the expression of the Cap protein in C. reinhardtii transformants. The results of the study showed that the ORF2 antigen gene had been correctly integrated into the specific site of the C. reinhardtii chloroplast genome, and the Cap protein was effectively expressed. These results suggested that the C. reinhardtii chloroplast is a potential platform for the production of recombinant antigen proteins and provided important support for exploring new production pathways of recombinant pharmaceutical proteins.